The Role of Structural Reforms in Raising Economic Growth in Central America - Swiston, Andrew; Barrot, Luis. (Washington, D.C. : International Monetary Fund, 2011)
Central America experienced moderate growth during the last decade, including in the years leading up to the global financial crisis, but the rate of convergence toward advanced country income levels has still been slow. Moreover, forecasts imply that these trends will continue. What can be done to spur higher growth in Central America? We bring new data to bear on this question-version 7.0 of the Penn World Table and a new IMF database on structural reforms. Our cross-country panel regression of economic growth using System GMM captures the importance to growth of conditional convergence, factor accumulation, and macro policies. In addition, structural efficiency is a significant factor in explaining growth performance. We construct a broad index of efficiency and find that increasing the degree of structural efficiency by one standard deviation raises growth by 1\2 percent. This implies that Central American countries could significantly increase their long-run growth rates by increasing the flexibility of markets and improving the quality of regulation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet